An exploration of young people in care’s experiences of school belonging in secondary school - Rodger, Erin (2023)
Young people in care continue to be at an educational disadvantage in comparison to their peers who are not in care, despite government initiatives (Education Committee, 2022; Sebba et al., 2015). School has been acknowledged in the literature as a protective factor for children and young people in care as it is suggested to provide opportunities for success facilitated through consistent and supportive relationships in a safe and predictable environment (Macleod et al., 2021). The importance of belonging for young people in care, adolescence and secondary education has been highlighted in the literature (Hyde & Atkinson, 2019), including the association between school belonging and educational success (Somers et al., 2020). However, a review of the school belonging literature highlighted that limited research has been conducted with young people in care in the UK that centred their individual school belonging experiences from their own perspectives.